Pengaruh Motivasi dan Kualitas Sumber Daya Manusia Terhadap Kinerja Karyawan di Hotel Bumi Senyiur Samarinda - Sitopu, Andrew Einstain; Saputra, Bobby W. (Syntax Literate, 2025)
This study aims to determine the effect of motivation and human resource quality on employee performance at Hotel Bumi Senyiur Samarinda. The hospitality industry faces challenges in maintaining optimal employee performance amid increasingly fierce competition. The research method uses a quantitative approach with a survey design of 109 respondents from Hotel Bumi Senyiur Samarinda employees selected using the Slovin formula. Data collection techniques used questionnaires with Likert scale, interviews, and observations. Data analysis used multiple linear regression with SPSS assistance. The results showed that motivation has a positive and significant effect on employee performance with t-count value 7.569 > t-table 1.659 and significance 0.001 < 0.05. Human resource quality has a positive and significant effect on employee performance with t-count value 12.249 > t-table 1.659 and significance 0.001 < 0.05. Simultaneously, motivation and HR quality significantly affect employee performance with F-count value 81.307 > F-table 3.08 and contribution of 60.5%. This research provides practical implications for hotel management to develop targeted motivation systems and improve HR quality through continuous training programs to enhance organizational competitiveness.